THE EFFECT OF MANAGERIAL OWNERSHIP, WOMEN CEO AND WATER ACCOUNTING ON PROFIT MANAGEMENT - Sarra, Hustna Dara; Mardania, Desi (Universitas Muhammadiyah Tangerang, 2025)
This research was conducted to determine the effect of managerial ownership, female CEO and water accounting on earnings management in manufacturing companies listed on the IDX in 2018-2022. This research uses quantitative research. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange (BEI). The sampling technique uses a purposive sampling method based on several predetermined criteria and produces 10 company samples with 50 observation data. The data analysis method used panel data regression analysis which is tested using Eviews 12 software. The hypothesis testing method uses a significance level of 5%. The research results show that the managerial ownership and woman CEO variables have an effect on earnings management, while the water accounting variable has no effect on earnings management.